Structural, optical, and mechanical properties of cobalt copper oxide coatings synthesized from low concentrations of sol–gel process. Issue 12 (17th August 2016) - Amri, Amun; Jiang, Zhong‐Tao; Yin, Chun‐Yang; Fadli, Ahmad; Rahman, Mohammad Mahbubur; Bahri, Syaiful; Widjaja, Hantarto; Mondinos, Nicholas; Herawan, Tutut; Munir, Muhammad Miftahul; Priyotomo, Gadang
Abstract : Thin films of Co x Cu y O z have been coated on aluminum substrates via sol–gel route using low concentration of copper and cobalt precursors at annealing temperatures in range of 500–650 °C. The coatings were characterized by X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), UV‐Vis‐NIR spectrophotometry, and nanoindentation. The XRD analysis in 2 θ ‐range of 30°–42° revealed that the coatings exhibited low crystallinity of CoCu2 O3, CoCuO2, and CuCoO2 . The surface bonding structure analyzed using XPS indicated that the coating contained: Cu (tetrahedral Cu + and octahedral Cu 2+ ), Co (octahedral Co 3+, tetrahedral Co 2+, and mixed Co 2+ and Co 3+ ), and O (lattice, surface, and sub‐surface oxygens). The optical properties characterized using UV‐Vis‐NIR showed that the reflectance spectra of coatings formed a spectrally solar selective absorber profile associated with the interference peaks and the absorption edges around wavelengths of below 1.2 μm. The maximum absorptance ( α = 75.8%) was shown by coating synthesized at 500 °C. The mechanical properties of coatings showed that the increase of annealing temperature increased the coating's hardness ( H ) and the elastic modulus ( E ) due to the enhancement of the [CoCuO2 /CuCoO2 ]:[CoCu2 O3 ] oxide phases ratio, as the result, an excellent stability of the wear resistance ( H/E ) of around ∼0.035 was recorded.